Malgortoute Sugar Estate, Trinidad - (:unkn) unknown (My University, 2009)
A picture of the operations at Malgortoute Sugar Estate which was located near Princes Town, south-west Trinidad.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Sugarcane industry--Trinidad and Tobago; Sugarcane--Trinidad and Tobago; Working class--Trinidad and Tobago; Sugar factories--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Men--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; [1910]